Gambaran Tingkat Kepatuhan Penata Anestesi dalam Penggunaan Alat Pelindung Diri (APD) di Kabupaten Cilacap - Mochamad Bayu Nuryatmaja; Danang Tri Yudono; Magenda Bisma Yudha (Pusat Riset dan Inovasi Nasional, 2025)
The use of Personal Protective Equipment (PPE) by health workers is very important in preventing the transmission of infections, especially in the Central Surgical Installation (IBS) room which has a high risk. Anesthesia organizers are health workers who are vulnerable to exposure to infection because they often perform actions that are in direct contact with the patient's body fluids. The purpose of this study was to identify the characteristics of the level of compliance of anesthesiologists in the use of PPE based on gender, age, education level and length of work in hospitals in the Cilacap Regency Region. This study is quantitative descriptive with a cross dectional approach. The research population is 38 respondents, the focus of observation in this study is an overview of the compliance of anesthesiologists in the use of personal protective equipment (PPE) in Cilacap Regency. This study showed compliance in the use of PPE with the compliant category as many as 24 respondents (63.2%), less compliant as many as 11 respondents (28.9%), while non-compliance as many as 3 respondents (7.9%). The results of this study show that there is compliance, lack of compliance, and non-compliance with anesthesia surgeons in Cilacap Regency.